Availability Indices of Boron in Tropical Acidic Rice Soils - P. Sureshkumar, Anu George and (Journal of the Indian Society of Soil Science, 2016)
Characterization of major soil groups of Kerala with respect to their boron (B) supplying power has been done using azomethine-H method. Fractionation study was conducted to quantify the major fractions contributing to B fertility. Adsorption studies were also conducted to find out B adsorption pattern of selected soils by using quantity/intensity factors. Fifteen soils out of the 25 soils under study had hot water extractable B content less than the critical limit (0.5 mg kg-1). Non-specifically adsorbed plus water soluble fraction (NSA-B) and Mn-oxy hydroxide fraction (MOH-B) contributed to the plant available pool. Adsorption of B for 22 soils could be described by Freundlich equation.